Cancer among patients with type 2 diabetes mellitus: A population-based cohort study in northeastern Italy. (April 2016) - Gini, Andrea; Bidoli, Ettore; Zanier, Loris; Clagnan, Elena; Zanette, Giorgio; Gobbato, Michele; De Paoli, Paolo; Serraino, Diego
Highlights: A population-based cohort study of cancer in 32, 247 type 2 diabetes mellitus (T2DM) patients. T2DM patients had an overall 28% significantly higher cancer risk. Particularly elevated risks were found for liver and pancreas carcinomas. T2DM patients with breast cancerhad a lower 5-year survival probability than breast cancer patients without diabetes. Abstract: Diabetes mellitus (DM) is associated with an elevated risk of cancer. The aim of this study was to assess cancer risk and survival in individuals with type 2 DM (T2DM) in Friuli Venezia Giulia, Italy. A retrospective population-based cohort study of 32, 247 T2DM patients aged 40–84 years was conducted through a record linkage of local healthcare databases and cancer registry for the period 2002–2009. Standardized incidence ratios (SIRs) with 95% confidence intervals (95%CIs) and 5-year survival probabilities after T2DM and cancer diagnosis were computed. The SIRs for all cancers ( n = 2069) was 1.28 (95%CI: 1.23–1.34). The highest SIRs were observed for cancers of the liver, female genital organs, small intestine, and pancreas. After 3 years from T2DM diagnosis, a reduced risk of prostate cancer (SIR = 0.73, 95%CI: 0.54–0.96) was found in men aged 65–74 years, and a higher risk for breast cancer (SIR = 1.24, 95%CI: 1.00–1.52) was found among T2DM female patients. The overall 5-year survival after T2DM was 88.7%. Furthermore, T2DM appeared to have a negative effect on survival of women with breast cancer. This population-based study confirmed that T2DM patients are at increased risk of several cancers, and of premature death in women with breast cancer.